Indeks Massa Tubuh Sebagai Faktor Risiko Pada Gangguan Muskuloskeletal - Redina Andini (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Body mass index (BMI) has proven as one of the risk factors for musculoskeletal disorders. overweight and obesity cause in several musculoskeletal disorders. Rheumatoid Arthritis (RA) is a chronic autoimmune disease and obesity is a risk factor of it. Regarding osteoarthritis (OA), overweight accelerates damage to the structure of the joint cartilage. overweight causes inflammation of the plantar fascia, called plantar fasciitis. Obesity causes lower back pain due to mechanical and inflammatory factors. Underweight causes bone mineral density disturbance so it is more susceptible to osteoporosis.